Community study of dragon’s blood palm (Daemonorops spp.) in Harapan Rainforest, Sumatra - Revis Asra; JOKO RIDHO WITONO; IZUANDRY FIJRIDIYANTO; ELVA; STEFAN SCHEU (Society for Indonesian Biodiversity, 2019)
Abstract. Asra R, Witono JR, Fijridiyanto I, Elva, Scheu S. 2019. Community study of dragon’s blood palm (Daemonorops spp.) in Harapan Rainforest, Sumatra. Biodiversitas 20: 3632-3640. Dragon's blood palms are rattan species that produce red-colored exudate on its fruit skin, popularly called exudates 'dragon's blood'. It has a high economic value and plays an important role as an income source for indigenous tribes in Jambi, such as in Bukit Duabelas National Park who live Anak Dalam Tribe and Semerantihan Village live Talang Mamak Tribe. However, overexploitation and unsustainable harvesting method have caused its decline in its population in natural forest. This study aims to make an inventory and map distribution of Dragon's blood palms in Harapan Rainforest, at the boundary between Jambi and South Sumatra Provinces, Indonesia; to determine its sex ratio and identify environmental factors that influence sex of Dragon's blood palms. This research used purposive random sampling method at three areas in Harapan Rainforest, i.e.: Hamparan Bato, Hamparan Batang Kapas, and Hamparan between Block A and B. The results showed that three species of Daemonorops were found in Harapan Rainforest, namely Daemonorops didymophylla, D. draco, and D. longipes. D. longipes has the highest population (18 clumps). The highest number of clumps were found in Hamparan Bato (17 clumps)and Hamparan Batang Kapas (17 clumps) areas. The ratio of male and female plants of D. longipes is 1: 1.84, D. draco is 1: 2 and D. didymophylla is 2.2: 1. Most clumps of Daemonorops species in Harapan Rainforest grow on the river banks which have low organic matters. Soil chemical variables that most contribute to the growth of Daemonorops spp. in Harapan Forest are N, C and pH.